Answer:
(11/15)'s
Step-by-step explanation:
(2/5) is equal to (6/15)
(1/3) is equal to (5/15)
(5/15)+(6/15)=(11/15)
Answer:
Simplifying
3x + 77 = 4x + 54
Reorder the terms:
77 + 3x = 4x + 54
Reorder the terms:
77 + 3x = 54 + 4x
Solving
77 + 3x = 54 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
77 + 3x + -4x = 54 + 4x + -4x
Combine like terms: 3x + -4x = -1x
77 + -1x = 54 + 4x + -4x
Combine like terms: 4x + -4x = 0
77 + -1x = 54 + 0
77 + -1x = 54
Add '-77' to each side of the equation.
77 + -77 + -1x = 54 + -77
Combine like terms: 77 + -77 = 0
0 + -1x = 54 + -77
-1x = 54 + -77
Combine like terms: 54 + -77 = -23
-1x = -23
Divide each side by '-1'.
x = 23
Simplifying
x = 23
Step-by-step explanation:
I hope its helps
Answer:
-2 but i may be wrong i am sorry if i am wrong
Step-by-step explanation:
Answer:
A. (3/5, 0).
Step-by-step explanation:
The x intercept occurs where y = 0, so we have:
5x + 7(0) = 3
5x = 3
x = 3/5 so the required point is (3/5, 0).